The Influence of Undergraduate Entrepreneurship Education on Entrepreneurial Intention: Evidence From Universities in China’s Pearl River Delta - Li, Jing; Huang, Shi-zheng; Chau, Ka Yin; Yu, Liqiong (Frontiers in Psychology, 2021)
Entrepreneurship may be taught, and entrepreneurship education is flourishing at colleges and universities. However, previous documents show that the entrepreneurship education is inconsistent with the research conclusions of entrepreneurial intention, which is lack of the discussion on the mediating effect of government subsidies from external resources. Based on the cognitive behavior theory, a mediating effect of entrepreneurship education on entrepreneurial strategy and entrepreneurial intention is built. By collecting the data of 334 questionnaires of college students in Pearl River Delta in China, structural equation is used for empirical analysis. The result indicates that: entrepreneurship education does not have a significant influence on entrepreneurial intention; exploration innovation and exploitation innovation have a positive influence on entrepreneurial intention, and exploration innovation and exploitation innovation have a mediating effect on entrepreneurship education and entrepreneurial intention; government subsidies have a positive regulating effect on exploration innovation, exploitation innovation and entrepreneurial intention. In this paper, the application of the cognitive behavior theory in the field of entrepreneurship research is expanded to provide the theoretical basis for building the entrepreneurship education ecosystem, which is conductive to innovation and entrepreneurship to promote the regional economic development.